Old acquaintances and new perspectives into testicular development and function - Cisneros Montalvo, Sheyla (fi=Turun yliopisto|en=University of Turku|, 2020)
Testicular development and function are complex processes that involve synchronization of the proliferation, apoptosis, and differentiation of specific somatic and germ cells to ensure lifelong fertility. Dysregulation of the signaling pathways or molecular mechanisms underlying these biological events often causes male infertility. With the increase observed in male fertility disorders worldwide, it is important to understand the origin of these conditions to be able to develop therapeutic strategies to alleviate or cure them in the future. The aim of this thesis is to describe the function of specific proteins in testicular development and function. Upstream stimulatory factor 1 (USF1) is a transcription factor that plays multiple roles in biological systems. In the testis, USF1 is reported to be expressed in Sertoli cells (SCs) and to bind specific genes during the differentiation of SCs. However, it remains elusive whether USF1 plays a role during spermatogenesis. Retinoblastoma protein (RB) and its associated E2F3 transcription factor are the regulators of various cellular events, such as mitosis, apoptosis, meiosis, and differentiation. We have previously shown that RB and E2F3 regulate adult SC function in the testis; however, the mechanism underlying this regulatory process is still unclear. Plasmalemma vesicle-associated protein is an endothelial-cell-specific membrane protein that is expressed in stomatal and fenestral diaphragms of a subset of endothelial cells. This protein regulates vascular permeability, leukocyte migration, and angiogenesis in different tissues; however, its role in the function of the testis has not yet been elucidated. Overall, this thesis comprises four studies. In the first study, a flow-cytometrybased method is developed to allow the rapid cell composition screening of fresh and cultured testicular tissues. In the second study, USF1 was shown to be expressed in spermatogonial stem cells, where it regulates the balance between spermatogonial stem cell self-renewal and differentiation. In the third study, the role of E2F3 during testicular development and the interaction between E2F3 and RB to maintain adult SC function were investigated. In the last study, the importance of plasmalemma vesicle-associated protein is revealed in the endocrine regulation of the testis.

Vanhaa ja koettua sekä uusia näköaloja kiveksen kehitykseen ja toimintaan Kiveksen kehitys ja siittiötuotanto ovat monimutkaisia ja tarkoin säädeltyjä prosesseja. Somaattisten solujen ja itusolujen oikea-aikainen jakautuminen, solukuolema ja erilaistuminen ovat edellytyksenä miesten elinikäiselle hedelmällisyydelle. Miesten hedelmällisyyden häiriöt ovat lisääntyneet maailmanlaajuisesti, minkä vuoksi on tärkeää ymmärtää niiden syntyyn vaikuttavia molekulaarisia ja solutason mekanismeja, jotta tulevaisuudessa voidaan kehittää hoitoja niiden lievittämiseksi ja parantamiseksi. ’Upstream stimulatory factor 1 (USF1)’ on transkriptiotekijä, jolla on useita tehtäviä eri kudoksissa. Kiveksessä sitä tiedetään tuotettavan Sertolin soluissa, joissa se niiden erilaistuessa sitoutuu useiden geenien säätelyalueille. On kuitenkin epäselvää, mikä on USF1:n merkitys hiiren siittiötuotannossa. Retinoblastoomaproteiini (RB) ja siihen liittyvä transkriptiotekijä E2F3 säätelevät useita solun tapahtumia, kuten jakautumista, solukuolemaa, meioosia ja erilaistumista. Olemme aiemmin osoittaneet, että kiveksessä RB yhdessä E2F3:n kanssa säätelee Sertolin solujen toimintaa, mutta taustalla vaikuttavaa säätelymekanismia ei tunneta. ‘Plasmalemma vesicle-associated protein’ (PLVAP) on soluspesifinen endoteliaalinen kalvoproteiini, joka ilmentyy aukkoisissa ja ikkunallisissa kalvoissa osassa endoteelisoluja. Se säätelee verisuonten läpäisevyyttä, valkosolujen läpäisyä ja verisuonten muodostusta eri kudoksissa, mutta kiveksessä sen tehtävää ei ole vielä tutkittu. Tämä väitöskirja koostuu neljästä eri tutkimuksesta: virtaussytometrisestä menetelmästä ja kolmesta muusta osatyöstä, joissa tutkimme USF1:n, RB/E2F3- vuorovaikutuksen ja PLVAP:n merkitystä kiveksen kehityksessä ja toiminnassa eri hiirimalleilla. Virtaussytometrinen menetelmä mahdollistaa nopean solukoostumuksen selvityksen tuoreesta tai viljellystä kiveskudoksesta. Toisessa osatyössä osoitettiin USF1:n ilmentyvän myös ituradan kantasoluissa, joissa se säätelee kantasolujen uusiutumisen ja erilaistumisen välistä tasapainoa. Kolmannessa osatyössä tutkittiin E2F3:n merkitystä kiveksen kehityksessä ja sen vuorovaikutusta RB:n kanssa aikuisen hiiren Sertoli solujen toiminnan ylläpitämiseksi. Väitöskirjan viimeinen osatyö osoitti PLVAP:n osallistuvan kiveksen kehityksen ja toiminnan hormonaaliseen säätelyyn.